Contributing to VRPN with a new server for haptic devices (ext. version) - Cuevas-Rodríguez, María; González-Toledo, Daniel; Molina-Tanco, Luis; Reyes-Lecuona, Arcadio (My University, 2015)
VRPN is a middleware to access Virtual Reality peripherals. VRPN standard distribution supports Geomagic® (formerly Phantom) haptic devices through the now superseded GHOST library. This paper presents VRPN OpenHaptics Server, a contribution to VRPN library that fully reimplements VRPN support of Geomagic Haptic Devices. The implementation is based on the OpenHaptics v3.0 HLAPI layer, which supports all Geomagic Haptic Devices. We present the architecture of the contributed server, a detailed description of the offered API and an analysis of its performance in a set of example scenarios.
This article is an extended version of the poster paper: Cuevas-Rodriguez, M., Gonzalez-Toledo D., Molina-Tanco, L., Reyes-Lecuona A., 2015, November. “Contributing to VRPN with a new server for haptic devices”. In Proceedings of the ACM symposium on Virtual reality software and technology. ACM.http://dx.doi.org/10.1145/2821592.2821639
Keywords: Realidad virtual; VRPN; Haptic devices; OpenHaptics; Phantom